PERLINDUNGAN HUKUM KONSUMEN DALAM TRANSAKSI FINANCIAL TECHNOLOGY (FINTECH) - Wahyu Utami (Yayasan Pendidikan Literasi Borneo, 2025)
The rapid development of financial technology (fintech) has significantly transformed the financial services sector, while simultaneously raising various legal issues, particularly regarding consumer protection. This study aims to analyze the legal protection of consumers in fintech transactions in Indonesia. The research employs a normative legal research method using statutory and conceptual approaches. The findings indicate that consumer protection in fintech transactions has been normatively regulated through the Consumer Protection Law and regulations issued by the Financial Services Authority. However, in practice, several challenges remain, including weak supervision, unfair standard clauses, and low levels of consumer legal literacy. Therefore, strengthening regulatory frameworks and effective law enforcement is essential to ensure adequate consumer protection in the fintech sector.